PENGARUH TEKNOLOGI INFORMASI DAN PENGGENDALIAN INTERNAL TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI PADA PEMERINTAH DAERAH KABUPATEN BIMA - Nurfailah Nurfailah; Maslichah Maslichah; Abdul Wahid Mahsuni (Universitas Islam Malang, 2022)
The purpose of this study was to examine the effect of information technology and internal control on the quality of accounting information systems in the Regional Government of Bima Regency, West Nusa Tenggara Province. The population used in this study were employees who worked at the Regional Government of Bima Regency, West Nusa Tenggara. Sampling was carried out as many as 60 employees, this study used a quantitative approach in collecting data using questionnaires and data analysis using descriptive statistics and multiple linear regression. The results of this study indicate that information technology and internal control have a significant effect on the quality of accounting information systems.Keywords: Information Technology and Internal Control on the Quality of Accounting Information Systems.